What can a dancing body do? The biopolitics of the Hobart Method with disabled subjects. Escape lanes in dance - Antonio Donato; Alessandro Bortolotti (University of Bologna, 2018)
This study provides an analysis of educational relationships developed through the artistic dance experiences of Hobart Method. By drawing on the emerging phenomenological paradigm of incorporation as frameworks, it becomes clear how such experiential activities allows the exploration of both personal and social habitus; and so, on the one hand, plausible explanations are provided to problematize the concepts of health and disease, and, on the other hand, to appreciate some interesting biopolitical effects. Ultimately, these artistic experiences, producing original instances such as subjectivation, allows participants to live self-governing practices: this makes it possible to animate real "escape lanes" from disciplinary apparatus, in order to modify the educational relashionship at a micropolitical level.